P94 Transforming acute care in COPD: findings from a national programme of service improvement. (2nd December 2011) - Thompson, C; Duncan, P; Blackaby, C; Lord, Z; Okosi, O; Wall, H; Porter, A
Abstract : Introduction: Respiratory disease presents a significant financial burden to the UK. 40% of the cost of managing respiratory disease is spent on hospital admissions. Admissions for respiratory disease account for 12% of all medical admissions and 94 000 are for exacerbation of Chronic Obstructive Pulmonary Disease (COPD). Between 1991 and 2001 admissions for COPD rose by 50% and data suggest the admissions trend continues to increase, representing an increasing burden to the NHS. The aims of this programme of work were to reduce admissions, readmissions at 30 days, length of stay (LOS) for exacerbation of COPD and to improve the quality of patient care and the patient's experience. Methods: Twelve project sites from primary care, secondary care and community services took part in an improvement workstream. They were supported by a national programme of information sharing and peer support. Service improvement methodology was used including a series of diagnostic tools. Secondary care data were used to demonstrate areas of duplication, bottlenecks and gaps within services. The Plan Do Study Act (PDSA) cycle was used to implement changes to services and to evaluate the impact of service redesign. Results: Data from five sites demonstrate £202k savings/cost avoidance through reductions in LOS and hospital admissions. Several important key learning points emerged from the programme of work: Cohorts of frequent attenders via the Emergency Department can be identified. One site identified 34 patients who accounted for 157 admissions in a 12-month period. Coordinated case management in this cohort may be effective in reducing admissions; data are not yet available to support this. Early access to specialist respiratory care is effective in reducing LOS. One site demonstrated a mean reduction in LOS of 0.4 days and another site a reduction of 1.5 days by instigating early specialist review. Improving communication and service integration is effective in reducing admissions. One site prevented 33 admissions through closer working between GP and Hospital at Home services. Conclusion: Effective service redesign can deliver improvements in the quality of respiratory services for patients with COPD and simultaneously deliver productivity gains and cost savings.